2020
DOI: 10.1016/j.ihj.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Study of saline optical coherence tomography–guided percutaneous coronary intervention (SOCT-PCI Study)

Abstract: Aim The aim of this study was to evaluate the feasibility of heparinised saline as flushing media for frequency-domain optical coherence tomography (FD-OCT) image acquisition during percutaneous coronary intervention (PCI) optimisation. Methods and results Twenty-seven patients undergoing FD-OCT–guided PCI were enrolled. Heparinised saline was injected into the coronary during FD-OCT image acquisition. A total of 118 runs were analysed for image quality and diagnostic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…The use in patients prone to CI-AKI is consequently limited. There is thus need for an alternative medium but neither low-molecular-weight dextran (LMWD) ( 151 ), nor heparinised saline ( 152 ), nor a mixture of saline and colloid ( 153 ) are ideal. Notably, LMWD is limited by its cost and slight risk of anaphylactoid reaction ( 154 ).…”
Section: Strategies To Prevent Contrast-induced Acute Kidney Injurymentioning
confidence: 99%
“…The use in patients prone to CI-AKI is consequently limited. There is thus need for an alternative medium but neither low-molecular-weight dextran (LMWD) ( 151 ), nor heparinised saline ( 152 ), nor a mixture of saline and colloid ( 153 ) are ideal. Notably, LMWD is limited by its cost and slight risk of anaphylactoid reaction ( 154 ).…”
Section: Strategies To Prevent Contrast-induced Acute Kidney Injurymentioning
confidence: 99%
“…This method does greatly reduce the volume of contrast agents used during PCI. SOCT PCI study was the first study to explore the feasibility, safety and efficacy of heparinized saline as flushing media for coronary OCT with the success rate of 88.1% (Effective runs for PCI that contains 61 good runs and 27.1% clinically usable runs) ( 12 ). Another study did head-to-head comparison of saline and contrast for image quality and measured vessel parameters and found it comparable ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that low-molecular-weight dextran (LMWD), which exhibits minimal toxicity compared to contrast agents, could be used as a flushing medium to acquire OCT images ( 8 10 ). Recently, studies also have evaluated the feasibility of heparinized saline as flushing media for OCT image acquisition during PCI optimization ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, its use is limited by the availability and risk of anaphylactoid reactions ( 106 ). Another medium that has been studied as an alternative to contrast is heparinized saline which has recently been demonstrated to be feasible and safe with acceptable image quality ( 107 ). One study showed that coronary dimensions measured using saline OCT were comparable to those obtained with contrast and hence saline OCT may be used as a contrast alternative for coronary OCT during PCI optimization ( 108 ) ( Figure 10 ).…”
Section: Contrast Sparing Octmentioning
confidence: 99%